2016
DOI: 10.1007/s10620-016-4331-y
|View full text |Cite
|
Sign up to set email alerts
|

Esophagogastric Junction Morphology and Distal Esophageal Acid Exposure

Abstract: A subset of patients with >2-cm LES-CD separation (type IIIb) maintain a physiological intra-abdominal location of the EGJ and are less likely to have reflux. A LES-CD ≥ 3 cm seems to discern a hiatus hernia of clinical significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 19 publications
0
9
0
1
Order By: Relevance
“…LES‐CD separation should be scored as the distance between the center of the CD and LES signal during inspiration, unless obscured in which case the LES position should be scored at expiration (Strong Recommendation). The EGJ complex should be defined based on LES‐CD separation and location of the RIP. (Low GRADE, Conditional Recommendation) 86–92 …”
Section: Esophagogastric Junction Metricsmentioning
confidence: 99%
See 1 more Smart Citation
“…LES‐CD separation should be scored as the distance between the center of the CD and LES signal during inspiration, unless obscured in which case the LES position should be scored at expiration (Strong Recommendation). The EGJ complex should be defined based on LES‐CD separation and location of the RIP. (Low GRADE, Conditional Recommendation) 86–92 …”
Section: Esophagogastric Junction Metricsmentioning
confidence: 99%
“…• The EGJ complex should be defined based on LES-CD separation and location of the RIP. (Low GRADE, Conditional Recommendation) [86][87][88][89][90][91][92] As for EGJ morphology, it was acknowledged that there were three subtypes: 1) normal with the CD superimposed on the LES and the RIP localizing proximal to the complex; 2) LES-CD separation with the RIP localized proximal to the CD; and 3) LES-CD separation with the RIP localized proximal to the LES. However, there was no consensus regarding the subtype classification scheme (I, II, III vs A, C, B) and both versions were deemed acceptable ( Figure S4).…”
Section: Additional Considerations For Ineffective Esophageal Motilitymentioning
confidence: 99%
“…8,9 Studies over the years have shown that a hiatal hernia, especially >3 cm, is associated with the most severe reflux. [10][11][12] Attention to the presence of these abnormalities is crucial to management decisions, especially regarding surgical intervention after eradication of Barrett's tissue.…”
Section: Underlying Pathophysiology Of Gerdmentioning
confidence: 99%
“…It is a quite old finding from animal [9] and human [10] studies that the crura of the diaphragm play an important role in closure of the lower esophagus [11]. Especially a dissociation of the lower esophageal sphincter from the position of the diaphragmatic crura as seen in hiatal hernia seems to be an important mechanism for gastroesophageal reflux [12,13]. It is straightforward to hypothesize that regular training of the striated muscle diaphragm can improve present reflux symptoms or may reduce the prevalence of GERD.…”
Section: Introductionmentioning
confidence: 99%